Role of tool pin profiles on wear characteristics of friction stir processed magnesium alloy ZK60/silicon carbide surface composites. Issue 2 (19th February 2020) - Vignesh Kumar, M.; Padmanaban, G.; Balasubramanian, V.
Abstract: Poor friction and wear resistance are the major drawbacks that restrict structural applications of ZK60 magnesium alloys. The surface properties of magnesium alloy can be enhanced by reinforcing particles in the surface using friction stir processing (FSP). Tool pin profile is the significant process parameters which influences the material flow, particle breakups and its distribution in the processed zone. In this study, an attempt was made in order to understand the major effects of tool pin profiles namely, cylindrical thread (CT), plain cylindrical (PC), plain tapered cylindrical (PTC) and square (SA) pin profiles on the microstructure characteristics and particle distribution of friction stir processed/silicon carbide particle surface composites. The surface composites fabricated by plain tapered cylindrical pin profile yield superior properties which is attributed to the higher shear force and balanced state of material flow and heat generation in the processed zone. The formation of smaller grains and hardness enhancement due to dispersion strengthening are the main causes to get better wear resistance of friction stir processed/silicon carbide particle magnesium alloy. Abstract : The surface properties of the lighter ZK60 magnesium alloy were improved by friction stir processing enabling reinforcement of silicon caride. The contribution of pin profiles on particle distribution and material flow on resultant processing soundness was analyzed. The enhancement of wear properties and the relation of hardness on wear was analyzed